Hidrologia e paleohidrologia da lagoa do - Cruz, Cláudia da (2012)
Banca Examinadora: Dr. Lafayette Dantas Luz (Orientador); Dr. José Maria Landim Dominguez(UFBA;)Drª Facelucia Barros C. Souza (UFBA;) Drª Alcina Magnólia Franca Barreto (UFPE); Dr. Francisco Hilário R. Bezerra (UFRN)